Pharyngeal pathology in a mouse model of oculopharyngeal muscular dystrophy is associated with impaired basal autophagy in myoblasts - Zhang, Yu; Zeuthen, Christopher; Zhu, Carol; Wu, Fang; Mezzell, Allison T.; Whitlow, Thomas J.; Choo, Hyojung J.; Vest, Katherine E. (Frontiers in Cell and Developmental Biology, 2022)
Oculopharyngeal muscular dystrophy (OPMD) is a late-onset dominant disease that primarily affects craniofacial muscles. Despite the fact that the genetic cause of OPMD is known to be expansion mutations in the gene encoding the nuclear polyadenosine RNA binding protein PABPN1, the molecular mechanisms of pathology are unknown and no pharmacologic treatments are available. Due to the limited availability of patient tissues, several animal models have been employed to study the pathology of OPMD. However, none of these models have demonstrated functional deficits in the muscles of the pharynx, which are predominantly affected by OPMD. Here, we used a knock-in mouse model of OPMD, Pabpn1+/A17, that closely genocopies patients. In Pabpn1+/A17 mice, we detected impaired pharyngeal muscle function, and impaired pharyngeal satellite cell proliferation and fusion. Molecular studies revealed that basal autophagy, which is required for normal satellite cell function, is higher in pharynx-derived myoblasts than in myoblasts derived from limb muscles. Interestingly, basal autophagy is impaired in cells derived from Pabpn1+/A17 mice. Pabpn1 knockdown in pharyngeal myoblasts failed to recapitulate the autophagy defect detected in Pabpn1+/A17 myoblasts suggesting that loss of PABPN1 function does not contribute to the basal autophagy defect. Taken together, these studies provide the first evidence for pharyngeal muscle and satellite cell pathology in a mouse model of OPMD and suggest that aberrant gain of PABPN1 function contributes to the craniofacial pathology in OPMD.